2009
DOI: 10.1016/j.bpa.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning techniques to examine large patient databases

Abstract: Computerization in healthcare in general, and in the operating room (OR) and intensive care unit (ICU) in particular, is on the rise. This leads to large patient databases, with specific properties. Machine learning techniques are able to examine and to extract knowledge from large databases in an automatic way. Although the number of potential applications for these techniques in medicine is large, few medical doctors are familiar with their methodology, advantages and pitfalls. A general overview of machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 40 publications
0
67
0
2
Order By: Relevance
“…However, machine-learning techniques have been used extensively in medicine, 21 in gene expression studies, [22][23][24] for classification of cardiac arrhythmias, 25 for predicting morbidity after coronary artery bypass surgery, 26 and for predicting when weaning from ventilator support should begin. 27 Gaussian processes have been applied in adults with ALI to model the pressure-volume curve to titrate PEEP.…”
Section: Discussionmentioning
confidence: 99%
“…However, machine-learning techniques have been used extensively in medicine, 21 in gene expression studies, [22][23][24] for classification of cardiac arrhythmias, 25 for predicting morbidity after coronary artery bypass surgery, 26 and for predicting when weaning from ventilator support should begin. 27 Gaussian processes have been applied in adults with ALI to model the pressure-volume curve to titrate PEEP.…”
Section: Discussionmentioning
confidence: 99%
“…The major requirement is to devise systems that detect patient-specific physiological states in real-time using minimally invasive and low power devices. The development in machine-learning algorithms that are capable of exploiting statistical properties in the data to model specific correlations will facilitate more accurate decision making by healthcare experts or devices [26]. For disease monitoring using machine learning models, prior pre-processing is as important, or even more important than the use of the machine learning models themselves [27].…”
Section: B Supporting Technologymentioning
confidence: 99%
“…Lynch et al [29] predicted lung cancer patient survival via supervised machine learning algorithms. Machine learning was also used in eHealth for analyzing patient's health data, predicting diseases, enhancing the productivity of technology or devices used for service providing, and so on [30], [31]. However, a very few studies [32]- [34] was found to predict the usage of eHealth among its target patients.…”
Section: Background and Objectivementioning
confidence: 99%